1993
DOI: 10.1111/j.1365-2672.1993.tb05138.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and attempted introduction of sugar alcohol‐utilizing bacteria in the sheep rumen

Abstract: Bacteria that use sorbitol, xylitol, maltitol and dulcitol (galactitol) were isolated from the sheep rumen following enrichments in which bacteria were grown in rumen fluid medium where the sugar alcohol was the only added energy source. Only isolates obtained with sorbitol and maltitol grew sufficiently rapidly to be considered for enrichment by the sugar alcohol in vivo. Isolate SS2, a strain of Selenomonas ruminantium var. lactilytica which grew on sorbitol at 0.87 h-1, was selected for further study and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Although these features serve as an anchor for studying the effect of different microbial makeups on the host over time (Li et al, 2009;Jewell et al, 2015), they also hinder the possibility of microbial manipulation and to follow the long-term effect of such changes. Most attempts at introducing bacteria, indigenous to the rumen, resulted in only a temporary The rumen microbiome and host physiology increase of the inoculum, followed by its decrease to extinction in a matter of days to a few weeks (Wallace and Walker, 1993;Krause et al, 2001a;Chiquette et al, 2008;Zebeli et al, 2012;Weimer et al, 2015). The microbiome is resilient to such an extent, that a recent study, which almost completely replaced the rumen fluid of one cow with the rumen fluid from another cow, showed that within just a few weeks, rumen microbiome content reverted to a content more closely resembling its original composition (Weimer et al, 2017).…”
Section: Potential Modulation Of the Rumen Microbiomementioning
confidence: 99%
“…Although these features serve as an anchor for studying the effect of different microbial makeups on the host over time (Li et al, 2009;Jewell et al, 2015), they also hinder the possibility of microbial manipulation and to follow the long-term effect of such changes. Most attempts at introducing bacteria, indigenous to the rumen, resulted in only a temporary The rumen microbiome and host physiology increase of the inoculum, followed by its decrease to extinction in a matter of days to a few weeks (Wallace and Walker, 1993;Krause et al, 2001a;Chiquette et al, 2008;Zebeli et al, 2012;Weimer et al, 2015). The microbiome is resilient to such an extent, that a recent study, which almost completely replaced the rumen fluid of one cow with the rumen fluid from another cow, showed that within just a few weeks, rumen microbiome content reverted to a content more closely resembling its original composition (Weimer et al, 2017).…”
Section: Potential Modulation Of the Rumen Microbiomementioning
confidence: 99%
“…was in fact reported as early as the 1930s (73). Sorbitol metabolism has also been observed by species of Selenomonas ruminantium in sheep rumen, suggesting this metabolic capacity may be widely distributed among microbes (74). Xylitol is generally regarded as beneficial in preventing oral lactobacilli, streptococci and actinomycetes growth; however, less is known about microbially mediated intestinal fermentation (75).…”
Section: Microbial Species Capable Of Fructose Sugar Alcohol and Artmentioning
confidence: 99%
“…Several groups of workers have dosed fibrolytic bacteria into the rumen but have found that the inoculant usually disappears from the rumen [223–226]. One of the reasons given for this is that we do not yet understand how fibrolytic bacteria exist and reproduce at the fiber surface.…”
Section: Improvement Of Fiber Digestion By Rumen Inoculationmentioning
confidence: 99%